Potential of using a new aluminosilicate amendment for the remediation of paddy soil co-contaminated with Cd and Pb. (15th January 2021) - Zhao, Hanghang; Huang, Xunrong; Liu, Fuhao; Hu, Xiongfei; Zhao, Xin; Wang, Lu; Gao, Pengcheng; Li, Xiuying; Ji, Puhui
Abstract: Cadmium (Cd) and lead (Pb) are toxic heavy metals that impact human health and biodiversity. Removal of Cd/Pb from contaminated soils is a means for maintaining environmental sustainability and biodiversity. In this study, we applied a newly modified material fly ash (NA), zeolite (ZE), and fly ash (FA) to the paddy soils and evaluated the effects of Cd/Pb accumulation in rice via a one-year field experiment. The results showed that the application of NA and ZE enhanced the soil pH and nutrients to a large extent and reduced the availability of Cd/Pb in soil. The Cd and Pb concentrations in rice grains decreased by 32.8% and 62.9%, respectively, with the NA treatments. Similarly, the application of ZE reduced the Cd and Pb concentrations in rice grains by a factor of 27.9% and 63.5%, respectively, which indicates that the amendments can promote the transfer of Cd and Pb from acid-exchangeable fraction to oxidizable and residual fractions. The Cd/Pb showed a significant positive correlation to other metal ions and a negative correlation to the nutrients. Generally, the application of NA and ZE was effective in reducing Cd/Pb accumulation and improving rice yield. Moreover, the NA was more cost-effective than ZE. Hence, this study proves that NA may be a better amendment for remediation of Cd/Pb contaminated soils. Graphical abstract: Image 1 Highlights: Fly ash modified material is used to control soils contamination. NA reduce the Cd/Pb accumulation while improve rice growth. Cd/Pb concentrations in rice grains are lower than 0.2 mg kg −1 after treatment. NA and ZE treatments no significant difference in soils remediation.